Alloying effects of Ag on grain boundaries and alumina interfaces in copper: a first principles prediction. Issue 76 (13th October 2017) - Teng, F.; Lan, G. Q.; Jiang, Y.; Song, M.; Liu, S. J.; Wu, C. P.; Yi, D. Q.
Abstract : The mechanical properties of oxide dispersion-strengthened copper are largely dictated by its internal interfaces, i.e. the oxide interfaces and the grain boundaries (GBs). Abstract : The mechanical properties of oxide dispersion-strengthened copper are largely dictated by its internal interfaces, i.e. the oxide interfaces and the grain boundaries (GBs). Here we present a systematic first-principles study for evaluating the potential impact of Ag alloying on adhesion of Cu/α-Al2 O3 interfaces and Cu grain boundaries as well. The results suggest that, in contrast to the strong segregation of S that is always detrimental, Ag only slightly segregates to the Al2 O3 interfaces, strengthens the weak stoichiometric interface, and slightly weakens the strong Al-rich interface. Ag cannot pin S inside the matrix. The co-segregation of Ag with S modestly negates the detrimental influence of S on adhesion, but can hardly occur. Ag segregation to most of the GBs is found also to be weak, and reduces the adhesion slightly. The only one exception is on the Σ9 GB. Based on the gained insights, we suggest that Ag alloying has only limited benefits but can still be encouraged.